The perspectives of allied health clinicians on the working alliance with people with stroke-related communication impairment. Issue 9 (21st October 2021) - Stagg, Kellie; Douglas, Jacinta; Iacono, Teresa
ABSTRACT: The processes by which working alliances develop in stroke rehabilitation are not well understood. The aim of this study was to explore the ways in which experienced allied health clinicians establish and maintain alliances with people with stroke-related communication impairment, and to identify factors that may influence the strength of these alliances. In-depth interviews were completed with 11 clinicians from the disciplines of occupational therapy, speech-language pathology and physiotherapy. Interview transcripts were coded and analysed using strategies consistent with constructivist grounded theory. Participants described processes that were captured by the themes of enabling interaction, being responsive, building relational capital and building credibility. Practices that supported communication and emphasized responding, both within an interaction and over time, aligned with examples of strong alliances. Professional credibility and relational practices such as everyday conversations and the use of humour were viewed as important. Difficulty accessing a shared mode of communication due to stroke-related communication impairment altered relational processes and influenced perceptions of the alliance, although examples of strong alliances were present. In this study, reflections on challenging alliances highlighted potentially helpful practices. A responsive approach to rehabilitation, supported by reflective practice, may assist clinicians to better navigate their working alliances with this population.